Tungstate Supported on Periodic Mesoporous Organosilica with Imidazolium Framework as an Efficient and Recyclable Catalyst for the Selective Oxidation of Sulfides. Issue 6 (11th March 2015) - Karimi, Babak; Khorasani, Mojtaba; Bakhshandeh Rostami, Fatemeh; Elhamifar, Dawood; Vali, Hojatollah
Abstract: A catalyst based on immobilization of tungstate ions (WO4 2− ) inside the mesochannels of periodic mesoporous organosilica comprising bridged ionic liquid (1, 3‐bis(3‐trimethoxysilylpropyl)imidazolium chloride) has been synthesized and characterized. This catalyst was then employed for the selective oxidation of organic sulfides to the corresponding sulfoxides or sulfones. The final synthesized catalyst was characterized by various techniques such as nitrogen sorption analysis, transmission electron microscopy, and thermogravimetric analysis. The catalyst was also applied to the selective oxidation of sulfides containing readily oxidizable functional groups such as hydroxyl, allylic, and even challenging aliphatic sulfides. Interestingly, it was found that on changing the reaction medium from aqueous methanol to aqueous acetonitrile, the product selectivity was changed successfully from sulfoxide to sulfone with good to excellent yields. Moreover, the catalyst can also be recovered and reused efficiently in nine subsequent reaction cycles without any remarkable decrease in the catalyst activity and selectivity. Abstract : Interior design : The tungstate ion supported on periodic mesoporous organosilica with an ionic‐liquid framework (see figure) has been used as an efficient and recoverable catalyst in the selective oxidation of organic sulfides into the related sulfoxides or sulfones, according to the choice of reaction solvent. The use of 30 % H2 O2 as a green oxidant was also achieved.